Governance vis-à-vis investment efficiency: Substitutes or complementary in their effects on disclosure practice - Noha Elberry; Khaled Hussainey (Journal of Risk and Financial Management, 2021)
Prior studies provide evidence that both corporate governance and corporate investment efficiency affect corporate disclosure practice. In this paper, we examine their joint effect on disclosure. In particular, we examine whether corporate governance quality and corporate investment efficiency act as substitutes or complements in their impact on narrative disclosure. We collect disclosure scores from Lancaster University's Corporate Financial Information Environment (CFIE) website for a sample of non-financial UK companies for the period 2007-2014. We regress measures of corporate governance and corporate investment efficiency on two different proxies of disclosure practice (performance commentaries disclosure and the tone of narrative disclosure). Consistent with prior studies, we find that both governance and investment efficiency affect disclosure. We contribute to narrative disclosure studies in two crucial respects. First, we provide empirical evidence that governance and investment efficiency has a complementary effect on performance commentaries disclosure. Second, we contribute to the disclosure tone literature by providing empirical evidence that both governance and investment efficiency have a substitution effect on the tone of narrative disclosure.
Keywords: 330; corporate governance; corporate investment efficiency; narrative disclosure; disclo-sure tone